2016
DOI: 10.1128/aem.03884-15
|View full text |Cite
|
Sign up to set email alerts
|

A TonB-Dependent Transporter Is Responsible for Methanobactin Uptake by Methylosinus trichosporium OB3b

Abstract: dMethanobactin, a small modified polypeptide synthesized by methanotrophs for copper uptake, has been found to be chromosomally encoded. The gene encoding the polypeptide precursor of methanobactin, mbnA, is part of a gene cluster that also includes several genes encoding proteins of unknown function (but speculated to be involved in methanobactin formation) as well as mbnT, which encodes a TonB-dependent transporter hypothesized to be responsible for methanobactin uptake. To determine if mbnT is truly respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…2A), with the ΔmbnT strain exhibiting much lower levels of 65 Cu. This result supports the experiments reported recently by Gu and coworkers (29).…”
Section: Gene Regulation Patterns Of Transport Proteins In Ms Trichosupporting
confidence: 83%
See 2 more Smart Citations
“…2A), with the ΔmbnT strain exhibiting much lower levels of 65 Cu. This result supports the experiments reported recently by Gu and coworkers (29).…”
Section: Gene Regulation Patterns Of Transport Proteins In Ms Trichosupporting
confidence: 83%
“…Recent quantitative RT-PCR (qRT-PCR) studies of Ms. trichosporium OB3b (32) revealed that these genes, including mbnE, are coregulated with mbnA and are all down-regulated in response to Cu addition. Taken together with the cessation of Mbn production in an mbnA deletion mutant (33) and the reported mbnT knockout strain (29), there is strong genetic evidence for the involvement of mbnT and mbnE in Mbn transport. However, the interaction of these proteins with Mbn has not been investigated biochemically.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…However, the observation that Csp3 is present alone in 22 methanotrophs (Csp1 is rarely present on its own) could indicate the function of this protein is independent of Csp1 and Mbn (see section about the functions of Csps). Much attention has been paid to the role of Mbn in Cu acquisition and utilization by methanotrophs (17,(50)(51)(52)(54)(55)(56)(57)(58)(59)(60). However, the currently identified Mbn operon is only found in just over 10% of sequenced methanotroph genomes, suggesting other systems are important for these processes.…”
Section: Csp Homologues In Other Methanotrophsmentioning
confidence: 99%
“…1, A and B) that is part of a highly specialized Cu-uptake system, secreted to sequester Cu under limiting conditions (17,50). The mbnA gene, which codes for leader (cleaved) and core (modified) peptides has been identified in an operon along with proteins either shown or suggested to be involved in modification reactions, apo-Mbn export, and re-incorporation of Cu(I)-Mbn (17,51,(55)(56)(57)(58)(59). Related Mbn operons are present in some non-methanotrophic bacteria (17,51,59).…”
mentioning
confidence: 99%